2009
DOI: 10.1021/cb900149b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of an Amphipathic α-Helical Peptide’s Antiviral Activity Involves Size-Dependent Virus Particle Lysis

Abstract: The N-terminal region of the hepatitis C virus (HCV) nonstructural protein NS5A contains an amphipathic alpha-helix that is necessary and sufficient for NS5A membrane association. A synthetic peptide (AH) comprising this amphipathic helix is able to lyse lipid vesicles that serve as a model system for virus particles. Based on quartz crystal microbalance-dissipation (QCM-D) experiments, the degree of vesicle rupturing was found to be inversely related to vesicle size, with maximal activity in the size range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
130
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(139 citation statements)
references
References 18 publications
7
130
0
2
Order By: Relevance
“…In this outlook, we introduce areas where we envision engineering strategies may further aid antiviral drug development. By assembling an in situ assay to predict virus particle rupture [40][41][42][43], the work reviewed here has established a cost-effective tool to rapidly screen and functionally characterize antiviral drug candidates in minutes rather than days. Based on this preliminary format, the system can be improved by increasing sensitivity to reduce the amount of peptide material required and/or adapting the signal response to a more readily high-throughput measurement technique.…”
Section: Outlook On Engineering Strategies For Antiviral Drug Developmentioning
confidence: 99%
See 2 more Smart Citations
“…In this outlook, we introduce areas where we envision engineering strategies may further aid antiviral drug development. By assembling an in situ assay to predict virus particle rupture [40][41][42][43], the work reviewed here has established a cost-effective tool to rapidly screen and functionally characterize antiviral drug candidates in minutes rather than days. Based on this preliminary format, the system can be improved by increasing sensitivity to reduce the amount of peptide material required and/or adapting the signal response to a more readily high-throughput measurement technique.…”
Section: Outlook On Engineering Strategies For Antiviral Drug Developmentioning
confidence: 99%
“…As a case study example of a viral pathogen target, we have selected the hepatitis C virus (HCV) and discuss how engineering strategies identified a previously unknown functional activity encoded within the HCV nonstructural 5A (NS5A) protein. By employing a model membrane platform to mimic the host cell membrane interface upon which viral genome replication occurs, a striking ability to lyse lipid vesicles was discovered within the NS5A N-terminal amphipathic, a-helix (AH) [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using quartz crystal microbalance with dissipation (QCM-D) monitoring, it was identified that AH peptide first adsorbs onto the vesicle surface, before destabilizing vesicles and causing vesicle rupture to form a planar bilayer [15]. In order to more clearly understand the mechanism of vesicle destabilization, simultaneous monitoring of the interaction between intact vesicles and AH peptide was performed with the QCM-D and reflectometry techniques [16]. It was identified that AH peptide binding causes an increase in solvent mass associated with the adsorbed vesicle layer prior to rupture.…”
Section: Introductionmentioning
confidence: 99%
“…These peptides often rely on their amphiphatic structure for their antiviral activity (Jenssen et al, 2004a;Yasin et al, 2000). Examples of synthetic antiviral peptides include both microbe-derived and hostderived peptide analogues, and these peptides can interfere with several medically important enveloped viruses (Cho et al, 2009;Mohan et al, 2010). The potential of using synthetic anti-microbial peptides (AMPs) against HSV is underscored by studies showing that synthetic derivatives of both human beta-defensins and frog magainins as well as several different families of synthetic peptides have anti-HSV activity in vitro (Egal et al, 1999;Jenssen et al, 2004a;Krepstakies et al, 2012;Luganini et al, 2011;Scudiero et al, 2010).…”
Section: Introductionmentioning
confidence: 99%